Isham White, The Laws and Ordinances of the City of Denver, Colorado 369, § 10 (1886) - (:unkn) unknown (My University, 1886)
Prohibited the carrying of any slungshot, colt, or metal knuckles while engaged in any breach of the peace. Punishable by a fine of $25-300.
Keywords: CARRY - INTENT TO COMMIT CRIME